2009
DOI: 10.1002/jsfa.3625
|View full text |Cite
|
Sign up to set email alerts
|

The response of phenylalanine ammonia‐lyase, polyphenol oxidase and phenols to cold stress in the olive tree (Olea europaea L. cv. Picual)

Abstract: BACKGROUND: In this study the activities of phenylalanine ammonia-lyase (PAL) and polyphenol oxidase (PPO) and the concentrations of hydroxytyrosol, tyrosol and oleuropein in olive tree (Olea europaea L. cv. Picual) leaves were investigated before and after cold stress by freezing. The air temperature fell to below −7• C and, according to the specific field conditions, four categories of orchard were selected: not cold stressed (NS), lightly cold stressed (LS), moderately cold stressed (MS) and heavily cold st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(47 citation statements)
references
References 51 publications
(61 reference statements)
3
37
0
1
Order By: Relevance
“…PPO enzyme also catalyses the oxidation of o diphe nols to o diquinones, as well as the hydroxylation of monophenols. PPO is important in the response of plants against freezing stress and it can help avoid seri ous oxidative damage induced by freezing [6].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PPO enzyme also catalyses the oxidation of o diphe nols to o diquinones, as well as the hydroxylation of monophenols. PPO is important in the response of plants against freezing stress and it can help avoid seri ous oxidative damage induced by freezing [6].…”
Section: Discussionmentioning
confidence: 99%
“…Then, POD and CAT convert H 2 O 2 into H 2 O and O 2 , whereas APX decomposes H 2 O 2 by oxidation of co substrates, such as phenolic compounds and/or antioxidants [5]. In addition, polyphenol oxidase (PPO) catalyzes the oxidation of o diphenols to o diquinones, as well as the hydroxylation of monophenols [6]. PPO is also an important enzyme in the response of plants against freezing stress, and it can help to avoid serious oxidative damage induced by freezing [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, interesting results to quantify cold tolerance have come from the study of some antioxidant enzymes (Solecka and Kacperska 2003;Cansev et al 2009;Ortega-García and Peragón 2009). A significant increase in the activity of CAT, APX and nicotinamide adenine dinucleotide phosphate (NADPH) oxidase as well as in dehydrin protein levels in cold-acclimatized olive trees was reported ).…”
Section: Introductionmentioning
confidence: 95%
“…At the same time, PAL is a sensitive indicator of stressful conditions and is commonly considered as a biochemical marker indicating the synthesis of both structural and protective compounds [32]. The study performed by Ortega-García and Peragón [33] showed that cold stress significantly stimulated PAL activity in leaves of the olive trees. Du et al [34] reported that enhanced UV-B radiation significantly increased PAL activity in fresh-cut carrot products.…”
Section: Enhanced Uv-b Effects On Biochemical Traits In Postharvest Fmentioning
confidence: 97%